General condition of the education system in regional countries (Journal of Pedagogical Inventions and Practices, 2022)
This article outlines the education system that existed in Central Asia in the late 20th and early 21st centuries. The shortcomings of the education system of the countries that gained independence from the USSR are revealed. In the early years of the decade, reforms implemented by governments were also briefly interrupted.